Global Variation of Human Papillomavirus Genotypes and Selected Genes Involved in Cervical Malignancies - R.S. Akram Husain; V. Ramakrishnan (Ubiquity Press, 2016)
Background: Carcinoma of the cervix is ranked second among the top 5 cancers affecting women globally. Parallel to other cancers, it is also a complex disease involving numerous factors such as human papillomavirus (HPV) infection followed by the activity of oncogenes and environmental factors. The incidence rate of the disease remains high in developing countries due to lack of awareness, followed by mass screening programs, various socioeconomic issues, and low usage of preventive vaccines. Over the past 3 decades, extensive research has taken place in cervical malignancy to elucidate the role of host genes in the pathogenesis of the disease, yet it remains one of the most prevalent diseases. It is imperative that recent genome-wide techniques be used to determine whether carcinogenesis of oncogenes is associated with cervical cancer at the molecular level and to translate that knowledge into developing diagnostic and therapeutic tools. Objective: The aim of this study was to discuss HPV predominance with their genotype distribution worldwide, and in India, as well as to discuss the newly identified oncogenes related to cervical cancer in current scenario. Findings: Using data from various databases and robust technologies, oncogenes associated with cervical malignancies were identified and are explained in concise manner. Conclusion: Due to the advent of recent technologies, new candidate genes are explored and can be used as precise biomarkers for screening and developing drug targets.